The Resurgence of African Religious Beliefs and Its Impact On Christianity in South Western Nigeria - Adesina, Julius Olu (KWASU Journal of Religious Studies, 2018)
The evangelism driven Christianity of the 19th century spear-headed by Townsend led to the advent of the Faith in Badagry in 1842. It subsequently led to the establishment of the first church in Nigeria, Abeokuta in 1898. This, however, appears to have waned considerably in the contemporary South Western Nigeria due to what can best be described as resurgence of African Religious (Afrel) beliefs. There is an apparent beclouding of basic Christian tenets which depicts in an unwholesome misinterpretation of Christian beliefs based on African Religion (Afrel) worldview. These are beliefs in God who need intermediaries to be approached. Hence popularity of false prophets and swindling Pastors among others. This paper in the light of the above interrogates this current trend with tested Christian values exemplified by Jesus Christ and popularized by the teaching and evangelism approach of Apostle Paul as gleaned in all his missionary journeys in Acts. The application of which has left vast regions of the world propagated effectively for Christ. The paper equally examines impediments on the path of sustained evangelism and revival of the Yoruba of South West Nigeria occasioned by the aforementioned resurgence. This is done with the intent of harping on the good side of African Religion (Afrel) such as belief in life after death using it as a platform for the parousia and Eschatology. The work adopts a qualitative approach to analyze collected data which are mainly from primary and secondary sources of books, journals, articles, internet and interviews embellished by inter disciplinary approach. It is discovered from the study that the current trend is amenable to inherent evangelism approach of earliest missionary persuasion of the aggressive type that made the pioneers of the religion to overcome daunting challenges. Consequently, the study recommends that ecumenical bodies with the Directorate of Evangelism and Revival at the international, regional, national and local levels be invigorated to curb this resurgence through periodical workshops and dissemination of information.